National recovery and resilience plan: Implications for Romania's agriculture - Aurelia Ioana Chereji; Irina Adriana Chiurciu; Ioan Chereji; Daniela Ţuţui; Cristina Maria Maerescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The COVID-19 pandemic crisis has generated a serious economic and social crisis in the European Union. This in return produced a vigorous EU reply that took among other the shape of a strong financial response trough the provisional instrument of the NextGenerationEU financial instrument. One of the key tools is the so-called Resilience and Recovery Mechanism that sees the allocation toward the Member States of important sums of money through grants and loans. The key rule to be followed by the Member States is to provide a National Recovery and Resilience Plan that underlines the measures taken by the State in order to reform its economy following the lines of a green and digital transition. The end outcome is to create a better economy that would withstand future shocks. Even though the emphasis is put on the green transition it also has an impact on the agricultural system. This impact may vary depending on each Member State ingenuity in drafting the targets to be reached in their National Recovery and Resilience Plans. In the case of Romania, we had a very ambitious agricultural component in the early drafts of the National Recovery and Resilience Plan that latter own following yet difficult to discern technical and administrative reasons were downgraded toward a more modest approach, both in scope and financial resources allocated to the agricultural sector, especially for reforestation and educational sector. The end hope is that the measures taken in adjacent sectors would have a positive spill over effect and that the agricultural sector would be the indirect beneficiary of these reforms.
Keywords: Q00; Z18; 330; National Recovery and Resilience Plan; agricultural sector; Romania; reforms; EuropeanUnion financing; COVID-19 pandemic